Arabidopsis phosphatidylinositol-phospholipase C2 (PLC2) is required for female gametogenesis and embryo development - Di Fino, Luciano Martin (2017)
Main conclusion: AtPLC2is an essential gene in Arabidopsis, since it is required for female gametogenesis and embryo development. AtPLC2 might play a role in cell division during embryo-sac development and early embryogenesis. Phosphoinositide-specific phospholipase C (PI-PLC) plays an important role in signal transduction during plant development and in the response to various biotic- and abiotic stresses. The Arabidopsis PI-PLC gene family is composed of nine members, named PLC1 to PLC9. Here, we report that PLC2 is involved in female gametophyte development and early embryogenesis. Using two Arabidopsis allelic T-DNA insertion lines with different phenotypic penetrations, we observed both female gametophytic defects and aberrant embryos. For the plc2-1 mutant (Ws background), no homozygous plants could be recovered in the offspring from self-pollinated plants. Nonetheless, plc2-1 hemizygous mutants are affected in female gametogenesis, showing embryo sacs arrested at early developmental stages. Allelic hemizygous plc2-2 mutant plants (Col-0 background) present reduced seed set and embryos arrested at the pre-globular stage with abnormal patterns of cell division. A low proportion (0.8%) of plc2-2 homozygous mutants was found to escape lethality and showed morphological defects and disrupted megagametogenesis. PLC2-promoter activity was observed during early megagametogenesis, and after fertilization in the embryo proper. Immunolocalization studies in early stage embryos revealed that PLC2 is restricted to the plasma membrane. Altogether, these results establish a role for PLC2 in both reproductive- and embryo development, presumably by controlling mitosis and/or the formation of cell-division planes.